Az első világháború következményei Közép-Európában - Majoros, István (Közép-Európai Közlemények, 2015)
The study presents the territorial changes after the First World War in Central Europe. Firstly the author examines the causes of the collapse of the Austro – Hungarian Monarchy at the end of the First World War. Then he presents the war plans of the Central Powers, first of all the German Mitteleuropa plan. He focuses on the Polish question, because Congress Poland belonging to Russia was occupied in 1915 by the Central Powers. France was also interested in this question because Poland was one of the elements of the German Mitteleuropa plan and it was dangerous for France and the antant countries. In the second part of the War the French diplomacy examined the possibilities how to change orientation in the French foreign policy after the war to counterbalance Germany. The French policy could have used the national commitees organized in Paris for example the Czechoslovak National Council, the Polish National Committee, etc. The map of Central Europe has been changed by the victorious countries after the First World War.